Becoming and being HIV-positive the subjective experience of young Filipino gay men living with HIV - Canoy, Nico A.; Ofreneo, Mira Alexis P. (Philippine Journal of Psychology, 2012)
"This research examined the lived experiences of young Filipino gay men living with HIV. Interpretative phenomenological analysis was utilized as the lens to explore patterns of meaning-making within a year after HIV diagnosis."